Media Sosial dalam Pembentukan Ketahanan Sosial Masyarakat Adat Kesepuhan Kawasan Taman Nasional Gunung Halimun - Fadhilah, Amir (Buletin Al-Turas, 2012)
Development as part of the government project, it sometimes does not involve the local community in the process of decision making. It is because the government tends to the mode of the top-down approach. As a return for this, the local community (villagers) is marginalized the development strategy imp/emendated recently, ignoring the indigenous knowledge system, where it reflects on cultural values of community and cares to the environment as the form of social capital owned by the community to become social tenacity.